1989
DOI: 10.1121/1.398740
|View full text |Cite
|
Sign up to set email alerts
|

Reverberant overlap- and self-masking in consonant identification

Abstract: Two effects of reverberation on the identification of consonants were evaluated for ten normal-hearing subjects: (1) the overlap of energy of a preceding consonant on the following consonant, called "overlap-masking"; and (2) the internal temporal smearing of energy within each consonant, called "self-masking." The stimuli were eight consonants/p,t,k,f,m,n,l,w/. The consonants were spoken in /s-at/context (experiment 1) and generated by a speech synthesizer in /s-at/ and/-at/contexts (experiment 2). In both ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
106
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 0 publications
5
106
0
Order By: Relevance
“…Reverberant sound energy typically creates a temporal "smearing" of speech that imposes overlap masking on contiguous phonemes, lengthens the durations of words, and fills quiet and/or low-intensity speech segments with unwanted sound ͑Bolt and MacDonald, 1949; Houtgast and Steeneken, 1985;Nabelek et al, 1989;Dreschler and Leeuw, 1990;Helfer, 1994;Culling et al, 2003͒. As a result, intelligibility decreases in conjunction with the reductions in speech envelope modulation depth imposed by temporal smearing ͑Houtgast and Steeneken, 1985͒.…”
Section: Introductionmentioning
confidence: 99%
“…Reverberant sound energy typically creates a temporal "smearing" of speech that imposes overlap masking on contiguous phonemes, lengthens the durations of words, and fills quiet and/or low-intensity speech segments with unwanted sound ͑Bolt and MacDonald, 1949; Houtgast and Steeneken, 1985;Nabelek et al, 1989;Dreschler and Leeuw, 1990;Helfer, 1994;Culling et al, 2003͒. As a result, intelligibility decreases in conjunction with the reductions in speech envelope modulation depth imposed by temporal smearing ͑Houtgast and Steeneken, 1985͒.…”
Section: Introductionmentioning
confidence: 99%
“…These portions have high energy and therefore cause a large amount of ''overlapmasking'' (i.e. reverberation tails mask the following phonemes) [6], but these portions are relatively less important for syllable perception compared with spectral transitions [7]. Therefore, SSS reduces the effect of overlap-masking with little degradation of the information needed for speech perception.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the main cause of degradation in speech intelligibility in reverberant environments is overlap-masking [3][4][5]. Because of overlap-masking, reverberant components of prior speech segments mask successive segments.…”
Section: Introductionmentioning
confidence: 99%